Pelatihan Penerapan Lubang Resapan Biopori Sebagai Penanggulangan Penumpukan Sampah Organik - A.A Istri Candra Manika Dewi; Rizal Wahyu Pratama; Khulika Malkan; Agung Malik Ibrahim; Jeti Aprilia; Syalaisha Nisrina Anataya (LPPM IT Telkom Purwokerto, 2024)
The accumulation of organic waste and the lack of soil infiltration has a negative impact on society, causing the spread of methane gas (CH4) in the air, which can worsen global climate change due to greenhouse effect conditions. Public awareness, especially among students, is not yet high enough to properly process organic waste. This community service aims to increase students' knowledge on how to process organic waste using a biopore system. The target of the activity is students of SMP Negeri 5 Purbalingga. The training participants were 27 students. The methods used were counseling and practice. The success of the activity is measured using the survey method. Counseling and practice sessions about biopores involve using two holes with a diameter of 10 cm and a depth of 100 cm. Both biopores were applied in the environment of SMP Negeri 5 Purbalingga. Based on a survey of participants using a questionnaire tool, the results showed that the level of knowledge of organic waste processing using the biopore system before counseling and training was 6.67% to 33.33%. After counseling and practice, the participants' knowledge increased to 73.33% - 93.33%. In conclusion, this counseling activity can increase the knowledge of students at SMP Negeri 5 Purbalingga on how to process organic waste with a biopore system. Therefore, based on this knowledge, it is hoped that the accumulation of organic waste can be reduced by the biopore system run by students and can reduce stagnant water due to rain.